2019
DOI: 10.1128/aem.01938-18
|View full text |Cite
|
Sign up to set email alerts
|

Siderophore-Mediated Iron Acquisition Enhances Resistance to Oxidative and Aromatic Compound Stress in Cupriavidus necator JMP134

Abstract: Many bacteria secrete siderophores to enhance iron uptake under iron-restricted conditions. In this study, we found thatCupriavidus necatorJMP134, a well-known aromatic pollutant-degrading bacterium, produces an unknown carboxylate-type siderophore named cupriabactin to overcome iron limitation. Using genome mining, targeted mutagenesis, and biochemical analysis, we discovered an operon containing six open reading frames (cubA–F) in theC. necatorJMP134 genome that encodes proteins required for the biosynthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 64 publications
3
25
0
Order By: Relevance
“…Here, three of the bioaugmentation candidates, P. putida OR45a, P. putida KB3, and S. maltophilia KB2, which had a high degradative potential towards aromatic compounds were found to successfully overcome the iron limitation by excreting siderophores. The literature data revealed that siderophores not only play an important role in iron scavenging but may also influence the swimming motility of bacteria as well as their resistance to oxidative and aromatic stress [65]. In our study, the relationship between siderophore production and the ability to withstand high concentrations of the KPL in wastewater was confirmed for two strains-P. fluorescens and Pseudomonas sp.…”
Section: Discussionsupporting
confidence: 75%
“…Here, three of the bioaugmentation candidates, P. putida OR45a, P. putida KB3, and S. maltophilia KB2, which had a high degradative potential towards aromatic compounds were found to successfully overcome the iron limitation by excreting siderophores. The literature data revealed that siderophores not only play an important role in iron scavenging but may also influence the swimming motility of bacteria as well as their resistance to oxidative and aromatic stress [65]. In our study, the relationship between siderophore production and the ability to withstand high concentrations of the KPL in wastewater was confirmed for two strains-P. fluorescens and Pseudomonas sp.…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, porphyrin and chlorophyll metabolism, the process from precorrin-2 to cobyrinic acid a,c-diamide in particular, was likely repressed, since the expression of all proteins in this process was found to be downregulated. Increased biosynthesis of enterobactin, which has been reported to protect cells against oxidative stress (25)(26)(27), was also observed. Besides, we observed increased expression of thioredoxin/glutathione peroxidase (BtuE, 1.64-fold) and catalase (KatE, 3.6-fold), which can remove reactive oxygen species (ROS) to protect cells (28).…”
Section: Resultsmentioning
confidence: 76%
“…baumannii strains AYE and DS002 were grown either in LB medium or in minimal salt medium [39] supplemented with phenol (2 mM) as the sole source of carbon at 30°C. The biofilm formation of the strains AYE and DS002 was determined following standard procedures [40].…”
Section: Methodsmentioning
confidence: 99%